The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1137/s0895480198348847
|View full text |Cite
|
Sign up to set email alerts
|

A New Property and a Faster Algorithm for Baseball Elimination

Abstract: Abstract. In the baseball elimination problem, there is a league consisting of n teams. At some point during the season, team i has w i wins and g ij games left to play against team j. A team is eliminated if it cannot possibly finish the season in first place or tied for first place. The goal is to determine exactly which teams are eliminated. The problem is not as easy as many sports writers would have you believe, in part because the answer depends not only on the number of games won and left to play but al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…The problem of determining when a sports team has mathematically clinched a playoff spot has been well studied for several sports, including baseball (Schwartz, 1966;Robinson, 1991;Wayne, 2001;Adler et al, 2002) and soccer (Ribeiro & Urrutia, 2005). The problem is known as a winner determination problem.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The problem of determining when a sports team has mathematically clinched a playoff spot has been well studied for several sports, including baseball (Schwartz, 1966;Robinson, 1991;Wayne, 2001;Adler et al, 2002) and soccer (Ribeiro & Urrutia, 2005). The problem is known as a winner determination problem.…”
Section: Related Workmentioning
confidence: 99%
“…However, their model could not be solved when secondary and tertiary tie-breaking rules were included. Wayne (2001) introduces the concept of a lower bound that could be used to determine whether or not a team was eliminated from the playoffs. Gusfield & Martel (2002) show how this idea can be extended to include a single wild card team.…”
Section: Related Workmentioning
confidence: 99%
“…Adler et al (2002) showed how integer programming can be used to compute the GQS and the PQS in the case of the MLB. Wayne (2001) showed that there exists a number of points such that every team is eliminated from the quest for the first place in the MLB if and only if it cannot reach this threshold. Gusfield and Martel (2002) generalized Wayne's result, showing that this threshold exists for every tournament with certain characteristics, including football leagues following the {(3, 0), (1, 1)} rule.…”
Section: Complexitymentioning
confidence: 99%
“…Different approaches for determining the minimum number of points guaranteeing playoff qualification have been previously applied for soccer [3], hockey [4][5][6][7], and baseball [8]. These sports feature matches between pairs of teams according to a prespecified schedule.…”
Section: Introductionmentioning
confidence: 99%